Game design e progresso em jogos: uma revisão bibliográfica para descrever um estudo teórico pratico do game design - Mastrochirico, Rodrigo Senice (2023)
This research fits into the field of video games, especially in terms of game design, with the aim of exploring the sense of progress that the game can produce in the player. This aspect is little studied in the field of literature on games, which justifies this study insofar as it seeks to understand the relationship between progress and the other elements that constitute digital games. We will try to understand if progress is a way to keep the player interested and motivated within a game and if, when we remove this attribute, we can say that one of the fundamental parts of this medium is lost